Preventive Measures and Safety Management in Construction A Case Study of Construction Work in Nonthaburi Municipality - Khunasangiamporn, Hirun; Kongsong, Waranon; Snongtaweeporn, Teeradej; Pooworakulchai, Chaiwat; Charoenrien, Sathian (Journal of Dhamma for Life, 2024)
The objective of this research is (1) to study the importance level of measures for preventing and managing safety according to the law concerning construction safety and (2) provide recommendations for measures to prevent and manage safety according to the law concerning construction safety. This is quantitative research using a questionnaire as a tool to collect data from construction staffs involved in construction projects for the research study. A total of 164 respondents were surveyed, and the collected data were analyzed statistically. The research findings indicate that the construction staffs consider the importance level of safety prevention and management measures to be high (Mean = 3.910, SD = 0.691), with the following breakdown: Personal Protective Equipment (PPE) is considered the most important safety measure ( = 4.042, SD = 0.737). Recommendations and guidelines related to safety management are highly valued ( = 3.993, SD = 0.687). Policies regarding knowledge dissemination and training for construction staffs are also highly valued ( = 3.945, SD = 0.769). Emergency response teams for post-accident assistance are considered crucial ( = 3.908, SD = 0.856). Hypothesis testing based on demographic data, including education level, job position, and work experience, reveals significant differences in the importance level of safety measures. Specifically, differences are observed in education level and job position across all dimensions of safety measures, except for experience, which does not significantly affect the importance level except in the aspect of safety prevention measures. In conclusion, education level, job position, and work experience are factors influencing the importance level of safety measures in construction work. Additionally, the research emphasizes the significance of providing recommendations, guidelines, knowledge, and training to ensure proper adherence to safety measures, thereby highlighting the importance of preventing and managing safety according to construction safety laws.